2009
DOI: 10.1001/jama.2009.1404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Supplementation and Depletion on Hypoxic Pulmonary Hypertension

Abstract: YPOXIA-INDUCED PULMOnary hypertensive disorders are a major cause of morbidity and mortality in respiratory and cardiac diseases and at high altitude. [1][2][3][4] Hypoxia causes pulmonary hypertension through hypoxic pulmonary vasoconstriction and vascular remodeling. 1 Convergent discoveries in the biochemistry of oxygen sensing and in cardiopulmonary physiology have recently established the importance of the hypoxia-inducible factor (HIF) family of transcription factors in regulating these processes. [5][6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
161
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 32 publications
7
161
2
1
Order By: Relevance
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…This interaction between iron, hypoxia and the pulmonary circulation is consistent with known effects of iron on the hypoxiainducible factor (HIF) family of transcription factors and involvement of HIF in regulating cardiopulmonary physiology [2][3][4]. Studies from several centres have subsequently confirmed a link between iron status and idiopathic pulmonary arterial hypertension, demonstrating that iron deficiency is unexpectedly common in this disease and independently worsens morbidity and mortality (recently reviewed by Rhodes et al [5]).…”
supporting
confidence: 70%
“…During this life-threatening phase, the authors report that the benefits of standard combination therapy in reducing right ventricular afterload were short-lived in the face of worsening hypoxia. Recent work from our group and others has introduced the possibility that intravenous iron may provide additional benefit in this setting.In healthy iron-replete men studied over 1 week at high altitude (equivalent to sea level FiO 2 *0.12) we found that established hypoxiainduced pulmonary hypertension was significantly reversed by a single 200 mg dose of intravenous iron sucrose [2]. This effect was evident within 4 h of infusion-rapid enough to be of possible benefit in offloading the right ventricle in the acute clinical setting.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…24,25 This has been mainly attributed to stabilization and transcription of hypoxia-inducible factors linked to contraction, proliferation, and migration of pulmonary artery smooth muscle cells. [25][26][27] Another proposed concept is that (ID-induced) anemia may limit the conversion of nitrite to nitric oxide, thereby inhibiting the antiproliferative and vasodilatation effects of nitric oxide on the pulmonary vasculature. [28][29][30] Because the present study did not include right heart catheterization, we can only hypothesize about the alterations in the pulmonary circulation in ID iPAH patients.…”
Section: Iron and The Lungsmentioning
confidence: 99%